Os Mecanismos de Monitorização da CSER realizados pelo Comité Europeu de Direitos Sociais: o Sistema de Relatórios e o Sistema de Reclamações Coletivas - Carvalho, Raquel (2017)
The recent economic crisis has revealed the importance of Social Rights and, thus, the need of their protection and effectiveness. At an international level, there are several legal instruments regarding political and civil rights but there aren’t so many focused on Social Rights. Therefore, the European Social Chart, as a complement of Human Rights European Convention, becomes an example of Social Rights protection, setting forth not only Social Rights but also proceedings aiming at their monitoring and effectiveness: the Report System and the Collective Complaint System. The analysis of both procedures it can be concluded that those proceedings do not fully comply with that kind of protection but they are definitely on the right path.